Science Learning Outcomes of Junior High School Students on The Topic of Global Warming : A Descriptive Study with Rasch-Logit Item Analysis - Rifda Nur Hikmawati Arif; Aulia Aura Yusmaputri; Hasanuddin Hasanuddin (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aimed to describe the science learning outcomes of Grade IX junior secondary students on the topic of global warming in North Luwu Regency through descriptive statistics and Rasch-logit item analysis. A quantitative descriptive design was employed involving 378 students from four public junior secondary schools (SMPN 1 Sabbang, SMPN 1 Masamba, SMPN 3 Sabbang Selatan, and SMPN 4 Masamba). The instrument consisted of 20 multiple-choice items aligned with cognitive levels C1–C4 of the revised Bloom’s taxonomy (Anderson & Krathwohl, 2015). Recalculation showed 5,583 correct responses, with an overall mean score of 14.77 out of 20, confirming the reported thesis mean of 14.76. Students’ achievement was categorised as high (Arikunto, 2018). SMPN 3 Sabbang Selatan obtained the highest mean score (17.20; very high category), whereas SMPN 1 Sabbang obtained the lowest mean score (13.85; high category). The KR-20 coefficient was 0.674, indicating moderate internal consistency. Item difficulty analysis showed that 13 items were easy, 7 items were moderate, and no item was difficult. The most difficult item was Item 18 (p = 0.415; logit = +0.342), while the easiest was Item 11 (p = 0.902; logit = −2.221). Wright Map visualisation indicates that the instrument needs more challenging items, particularly at C2–C4 levels (Bond & Fox, 2015; Boone et al., 2014).